A polymer material, electrolyte and battery

By using polymer materials containing phosphorus groups in lithium-ion batteries, the safety hazards of liquid electrolytes and the insufficient ionic conductivity of gel polymer electrolytes are solved, and the high safety and cycle stability of the battery are achieved.

CN115677931BActive Publication Date: 2025-02-07BEIJING WELION NEW ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110846758.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-07-26
Publication Date
2025-02-07
Estimated Expiration
2041-07-26

AI Technical Summary

Technical Problem

There are safety risks for liquid electrolytes in existing lithium-ion batteries, and gel polymer electrolytes lack ionic conductivity at room temperature, making it difficult to meet the needs of high-speed batteries.

Method used

Using a polymer material containing phosphorus groups, its structure includes -[M1-M2]-polymerization unit, a solid-state battery prepared by non-in-situ curing or in-situ curing methods, improves the safety performance and cycle stability of the battery. .

Benefits of technology

It significantly improves the safety and cycle stability of the battery, extends the battery life, and reduces the use and emission of organic solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115677931B_ABST
    Figure CN115677931B_ABST
Patent Text Reader

Abstract

The present application provides a polymer material, an electrolyte and a battery. The structure of the polymer material at least includes the ‑[M1‑M2]‑polymer unit shown in Formula 1. The polymer material containing phosphorus groups provided in the present application can be flexibly applied to batteries to improve battery safety, improve battery ion transport, improve battery cycle stability and extend battery life. #imgabs0#
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a polymer material, an electrolyte and a battery. Background Art

[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, long cycle life, low self-discharge rate and no memory effect, and have broad application prospects in the field of new energy electric vehicles. With the continuous development of science and technology, the requirements for the performance of lithium-ion batteries are getting higher and higher. With the continuous improvement of battery energy density, safety issues are becoming increasingly prominent.

[0003] Traditional LIBs mainly use liquid electrolytes, which contain a large amount of flammable organic carbonate solvents, which can easily lead to safety issues such as electrolyte leakage, thermal runaway or explosion. In view of the above shortcomings of traditional LIBs, people have found that all-solid-state electrolytes can solve the safety problems caused by liquid electrolytes, thereby improving the safety performance of LIBs. Therefore, solid-state batteries composed of all-solid-state electrolytes have gradually come into people's sight.

[0004] Polymer solid electrolytes are currently the most commonly used type of solid electrolytes. They have the advantages of light weight, flexibility, and easy processing, which help to maintain good solid-solid interface contact; however, polymer solid electrolytes also have a series of problems such as low room temperature ionic conductivity and large interface impedance.

[0005] Gel polymer electrolytes (GPEs) are formed by swelling of polymer matrix and plasticizer. They not only have the high ionic conductivity of liquid electrolytes, but also the polymer matrix in GPEs forms a cross-linked structure by chemical bonds or physical forces, which plays a role of skeleton support, fixes the flowing solvent molecules in the polymer gel skeleton, and the electrolyte as a whole is a non-flowing semi-solid state, which is easy to process and not easy to leak, thus improving the safety of the battery. Therefore, gel polymer electrolytes (GPEs) that can balance interface contact and ionic conductivity have received widespread attention and a lot of research in recent years.

[0006] Although gel polymer electrolytes have good ion transport capabilities and electrode compatibility, they still have shortcomings that limit their further application in lithium batteries.

[0007] First, the ionic conductivity of gel polymer electrolytes at room temperature often cannot meet the needs of high-rate batteries, and the lithium ion migration number of gel polymer electrolytes is low, which can easily cause the increase of internal polarization and internal resistance of the battery during the cycle, as well as the growth of lithium negative electrode dendrites.

[0008] Secondly, the gel network formed after the polymer swells has poor mechanical strength, which makes it difficult to meet the process requirements of actual production, namely battery assembly.

[0009] Finally, the plasticizer used in the gel polymer is basically a commonly used liquid electrolyte or an organic carbonate solvent.

[0010] For example, CN108682863A discloses a lithium battery polymer gel electrolyte, in which the plasticizers used are epoxy oleate and dimethyl carbonate. Although excellent ionic conductivity can be achieved, a large amount of flammable carbonate plasticizers exist in the polymer matrix, so that the lithium battery constructed with this electrolyte still has the potential risk of combustion and explosion, and it is difficult to completely solve the safety problem of high energy density batteries. Summary of the invention

[0011] In view of this, the embodiments of the present application provide a polymer material, an electrolyte and a battery to solve the technical defects existing in the prior art.

[0012] The present application discloses a polymer material, the structure of which at least includes a -[M1-M2]-polymer unit as shown in Formula 1:

[0013]

[0014] Wherein, M1 is selected from C, N, P, S, Si, and M2 is selected from C, O, N, P, S, Si;

[0015] R1-R4 are independently selected from any one of a chain or a ring with no, with or without a substituent;

[0016] R5-R6 are independently selected from any one of a chain or ring with no substituents, a chain or ring with no substituents, and a polymer unit formed based on a chain or ring. When R5 and / or R6 represent a polymer unit, it includes a -[M1-M2]- polymer unit or other polymer units different from -[M1-M2]-; if the polymer material structure is unfolded, a single -[M1-M2]- polymer unit is arranged in a block manner, in an alternating manner, in a periodic manner, in a gradient manner, or in a random manner with respect to a single other polymer unit.

[0017] When R5 and / or R6 are selected from a chain or a ring with or without a substituent, they represent the terminal groups of the polymer material, and the terminal groups are formed based on the residues after the reaction of the raw materials or the initiator.

[0018] represents a cyclic structure in which any two adjacent positions are P and O; A1 represents that any position of the cyclic structure can be substituted by a substituent;

[0019] m is selected from 0.01-1, such as 0.02, 0.05, 0.1, 0.2, 0.3, 0.5, 0.8, 1, etc., which means that there is one in every 1 / m -[M1-M2]-polymer units. Connected to M1 or M2. Can be omitted when m is 1.

[0020] p is selected from an integer between 10 and 10000, such as 10, 20, 50, 80, 100, 500, 1000, 2000, 3000, 5000, 6000, 8000, 10000, etc., which represents that there are p -[M1-M2]- polymerization units in the structure of Formula 1.

[0021] Here is an example to illustrate briefly. For example, if m = 0.1 and p = 20, it means that there are 20 polymerization units composed of -[M1-M2]- in the entire structure of Formula 1. These 20 polymerization units composed of -[M1-M2]- are respectively connected with two connected, and one M1 or M2 among every 10 -[M1-M2]- Other situations can be deduced in the same way and will not be described here.

[0022] The present application innovatively adds a polymer material containing The polymer unit of the structure can enhance the safety performance of the battery, improve the battery ion transmission, enhance the battery cycle stability and extend the battery life.

[0023] Specifically, if R1-R6 are independently selected from a chain, the chain is selected from a chain of 1 to 15 atoms, preferably a chain of 1 to 10 atoms, and more preferably a chain of 2 to 6 atoms, including a saturated carbon chain, an unsaturated carbon chain, a saturated hetero chain, and an unsaturated hetero chain; the atoms located on the chain are selected from C, S, N, O, P, B or Si.

[0024] If R1-R6 independently contain a ring, the ring is selected from a three- to eighteen-membered ring, preferably a four- to ten-membered ring, more preferably a five- to eight-membered ring, such as a five-membered ring, a six-membered ring, etc. The ring includes a monocyclic ring, a linked ring, a fused ring, a bridged ring or a spirocyclic ring, and the atoms on the ring are selected from C, P, S, Si, N or O, and the monocyclic ring includes a saturated carbocyclic ring, an unsaturated carbocyclic ring, a saturated heterocyclic ring, an unsaturated heterocyclic ring, an aromatic carbocyclic ring, and an aromatic heterocyclic ring. The ring preferably contains at least one -C=O.

[0025] The substituents include: H, halogen atoms, =O, =S, alkyl, heteroalkyl, alkenyl, heteroalkenyl, alkynyl, heteroalkynyl, hydroxyl, carbonyl, aldehyde, carbonate, haloformyl, carboxyl, ester, peroxy, amine (primary amine, secondary amine, tertiary amine, quaternary ammonium salt), imino (C=N), imide (C(=O)NC(=O)), azo, nitrate (RONO2), phosphate, thioether, disulfide, cyano, sulfonic acid, sulfonyl, amide, nitro, pyridyl, acyloxy, phenyl, benzyl, benzyloxy, phenoxy, acetyl, benzoyl, benzyloxycarbonyl and chains or rings containing the above groups. Any H in the above substituents can be substituted by halogen, preferably by F. F can cooperate with the phosphorus group to promote the effect of the phosphorus group.

[0026] Optionally, The cyclic structure represented by is selected from a single ring, or any one of a linked ring, a combined ring, a bridged ring, and a spiro ring formed based on the single ring;

[0027] Preferably, the monocyclic ring is selected from saturated or unsaturated five- to six-membered rings, and the linked rings, parallel rings, bridged rings and spiro rings are independently composed of two or more saturated or unsaturated five- to six-membered rings.

[0028] Optionally, the ring structure is selected from:

[0029]

[0030] Wherein, A1, A2, A3 represent that any position on the ring can be substituted by a substituent. The types of substituents are referred to the above substituents, which will not be repeated here.

[0031] Optionally, the ring structure is selected from a ring formed by 2 or 3 of the single rings;

[0032] Preferably, the adjacent ring to which P and O are located contains at least one heteroatom or is substituted by at least one substituent containing a heteroatom, wherein the heteroatom is selected from N, O, P, S, Si, and F.

[0033] Among them, the adjacent rings where P and O are located contain at least one heteroatom or are substituted by at least one substituent containing a heteroatom, which can effectively improve the compatibility and coordination between the ring structure and the phosphorus group, so that the two form an organic whole, promote the role of the phosphorus group, and thus improve the performance of the polymer material.

[0034] Optionally, R3 is Among them, R 31 Selected from C, N, P, R 32 , R 33are independently selected from none, or a chain consisting of 1-3 atoms, R 34 is selected from H or a substituent.

[0035] Preferably, R 34 Selected from Li or BF3Li. This can provide more mobile lithium ions and improve the ion transport of lithium batteries.

[0036] Optionally, The P atom in the molecule is directly connected to the C atom. In other words, except for O, the atoms connected to the P atom, whether located in the ring or in the chain, are all C atoms. The P atom is connected to the C atom instead of being directly connected to the heteroatom, so that the phosphorus group and the heteroatom can maintain a certain distance, which can better promote the role of the phosphorus group and help improve the safety of polymer materials.

[0037] Optionally, R5 or R6 is selected from a -[M3-M4]-polymeric unit, wherein the structure of the -[M3-M4]-polymeric unit is as shown in Formula 2:

[0038] Formula 2;

[0039] The structure of the polymer material can be expressed as:

[0040] Wherein, M3 is selected from C, N, P, S, Si, and M4 is selected from C, O, N, P, S, Si;

[0041] R7-R 11 Independently selected from any one of a chain or a ring with no, with or without a substituent;

[0042] n is selected from an integer between 5 and 1000, such as 20, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 800, 1000, etc., preferably 10-800, indicating that there are n -[M3-M4]- polymerization units in the structure of Formula 1.

[0043] When the polymer material structure is unfolded, the single -[M1-M2]-polymer units and the single -[M3-M4]-polymer units are arranged in blocks, alternating, periodically, in gradients, or randomly.

[0044] Alternatively, H1 represents a single -[M1-M2]-polymer unit H2 represents a single -[M3-M4]-polymer unit The “—” drawn on the left side of M1 and M3 and on the right side of M2 and M4 in H1 and H2 indicates that they are connected to other H1 or H2 polymerization units through this bond, and is not an abbreviation of -CH3.

[0045] In polymer materials, the arrangements between H1 and H2 include:

[0046] Arranged in blocks: H1-H1- H1-H1-H1-H2-H2-H2- -H2-H2; in this case, the first Indicates one or more repeated H1s. The second H2 represents one or more repeated arrangements;

[0047] Alternating: One or more H1s and one or more H2s are arranged alternately in sequence, such as H1-H2- H1-H2-H1-H2 -H1-H2 (one H1 and one H2 arranged alternately), H1-H1-H2 H1-H1-H2 (two H1s and one H2 arranged alternately), H1-H1-H1-H2 H1-H1-H1-H2 (three H1s and one H2 arranged alternately) are all possible, and will not be described in detail here. In this case, Indicates one or more repetitions of "H1-H2".

[0048] Arrange in a periodic manner: Multiple periods are formed by one or more H1 and one or more H2, and multiple periods are arranged in sequence; for example (H1-H2-H1-H1-H2-H2)- -(H1-H2-H1-H1-H2-H2), (H1-H1-H2-H1-H2)- -(H1-H1-H2-H1-H2) etc. are all acceptable. One bracket represents one cycle. Represents one or more repetitive cycles.

[0049] Arranged in a gradient manner: the composition of H1 and H2 changes gradually along the chain; for example, H1-H2-H1-H1-H2-H2-H1-H1-H1-H2-H2-H2 , Represents H1 and H2 that increase with the chain gradient.

[0050] Irregular arrangement: One or more H1 and one or more H2 are randomly arranged in a cross pattern. For example, H1-H2- H1-H2-H2-H2-H1-H1- -H2-H1, H2-H2- H1-H1-H2-H1-H2-H1- -H1-H2 etc. are all OK, so I won't go into details here. In this case, Indicates irregular repetition of H1 and H2.

[0051] Optionally, R9 is selected from a ring or chain containing at least one heteroatom, and any position of the ring or chain can be substituted by a substituent;

[0052] Preferably, R9 is selected from a ring or chain containing at least two heteroatoms and containing at least one =0 in the ring or chain;

[0053] More preferably, R9 is selected from:

[0054] Wherein, A1 and A2 represent that the atoms in the ring / chain can be substituted by a substituent.

[0055] In the structure represented by R9, A1 and A2 are preferably F, Li, or OLi.

[0056] Optionally, in the structure of the polymer material, m is selected from 1, p is selected from an integer between 30 and 8000, n is selected from an integer between 10 and 800, and p>n. The introduction of the -[M3-M4]-polymerization unit can form an organic whole with the -[M1-M2]-polymerization unit, and the interaction between the two groups can effectively improve the safety of the polymer material, and n is less than p, so that the overall compliance and mechanical properties of the material can be guaranteed.

[0057] Optionally, the polymer material is prepared by reacting at least raw material A, or at least raw material A and raw material B;

[0058] The structure of raw material A is The structure of raw material B is

[0059] It should be noted that in the technical solution provided in the present application, no matter what synthesis method or process is used, the polymer material provided in the present application can be formed by the reaction of raw material A itself or the polymerization reaction between raw material A and raw material B, and the product obtained by the polymerization of raw material A itself or the copolymerization of raw material A and raw material B may be more than one, for example, it may obtain a polymer in which monomers are arranged in a variety of different ways, and these polymers are all within the scope of protection of the present application.

[0060] The present application also provides an electrolyte, wherein the electrolyte comprises the polymer material as described above, or comprises the raw materials for preparing the polymer material as described above.

[0061] The present application also provides a battery cell, wherein the battery cell comprises the polymer material as described above, or comprises the raw materials for preparing the polymer material as described above.

[0062] The present application also provides a battery, which comprises any one or more of the following: the polymer material as described above, the raw material for preparing the polymer material as described above, the electrolyte as described above, and the battery cell as described above.

[0063] In addition, the battery also includes electrodes (positive electrode, negative electrode), separator, and packaging shell.

[0064] The positive electrode is selected from one or more combinations of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese oxide.

[0065] The negative electrode is selected from one or more combinations of graphite, silicon, soft carbon, hard carbon, silicon-carbon composite material, silicon-oxygen-carbon, lithium titanate, mesophase carbon microspheres, molybdenum disulfide, silicon oxide, silicon, metallic lithium or metallic lithium alloy.

[0066] The diaphragm is selected from one of a polyolefin diaphragm, a cellulose diaphragm, a polyimide diaphragm, a polyamide diaphragm, an aramid diaphragm, a PET non-woven fabric diaphragm, a ceramic coated diaphragm, a solid electrolyte coated diaphragm, and a PVDF coated diaphragm.

[0067] The packaging shell is selected from one of a soft-package aluminum-plastic film, a steel shell, an aluminum shell, and a cylinder.

[0068] Optionally, the battery is a hybrid solid-liquid battery or an all-solid-state battery.

[0069] Specifically, the battery is a hybrid solid-liquid lithium battery or an all-solid-state lithium battery.

[0070] The present application also provides an application of a polymer material in a battery, wherein the polymer material or a raw material for preparing the polymer material is placed in a battery component or a battery cell of the battery to prepare the battery.

[0071] Optionally, the polymer material is placed in a battery component or a battery cell of the battery to prepare the battery through an ex-situ curing process;

[0072] or placing the raw materials in a battery assembly or a battery cell of the battery to prepare the battery through an in-situ curing process;

[0073] Wherein, the battery assembly includes electrodes, a separator and an electrolyte membrane.

[0074] Optionally, the polymer material may be placed in the battery in an ex-situ curing manner including:

[0075] (1) placing the polymer material in a battery cell, which comprises:

[0076] The polymer material is first added into the electrolyte to be dissolved, and then injected into the prepared battery cell;

[0077] (2) placing the polymer material in a battery component of the battery, which comprises:

[0078] The polymer material is dissolved in a solvent and then coated on an electrode sheet, a diaphragm or formed into a separate film to form an electrode sheet, a diaphragm or an electrolyte membrane with a polymer material coating; or the polymer material is mixed in positive and negative electrode slurries to form a pole sheet containing the polymer material.

[0079] Wherein, the solvent includes one or more of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, butylene carbonate, methyl propyl carbonate, methyl formate, ethyl formate, propyl formate, butyl formate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, 8-valerolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 4-methyl 1,3-dioxolane, 2-methyl-1,3-dioxolane, ethylene glycol dimethyl ether and 1,3 dioxolane, cyclopentane, and dimethyl sulfoxide.

[0080] In the process of dissolving the polymer material in the solvent, an auxiliary agent is also added, and the auxiliary agent includes any one or more of the following: lithium salt, inorganic particles, and fast ion conductor.

[0081] The lithium salt is selected from one or more of lithium trifluoromethanesulfonate (LiCF3SO2), lithium bis(trifluoromethanesulfonic acid)imide (LiN(CF3SO2)2), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium chloride (LiCl), lithium iodide (LiI), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium hexafluoroarsenate (LiAsF6).

[0082] The inert inorganic particles are selected from SiO2, ZrO2, Al2O3, TiO2, BaTiO3, CeO2, CuO, ZnO, MnO, MnO2, silicates, aluminosilicates, borosilicates and formula A x B y O zAt least one inorganic particle in the group consisting of oxygen-containing salts, or any one of the functionalized inorganic particles, where A is an alkali metal or alkaline earth metal, B is selected from the group consisting of Al, Mn, Si, Ti, Zn, Zr, Fe, and Cu, and x, y, z are the numbers of the corresponding atoms such that the total charge of the oxygen-containing salt is 0.

[0083] The active fast ion conductor is an oxide solid electrolyte, and the oxide solid electrolyte particles include any one or a combination of at least two of the following compounds: Li1+x1Alx1Ge2-x1(PO4)3 with NASICON structure or its isomorphous heteroatom-doped compounds, Li1+x2Alx2Ti2-x2(PO4)3 or its isomorphous heteroatom-doped compounds, Li3x3La 2 / 3 -x3TiO3 or its isomorphous heteroatom-doped compounds, Li 3 / 8 Sr 7 / 16 Ta 3 / 4 Hf 1 / 4 O3 or its isomorphous heteroatom-doped compounds, Li2x4-y1Sr1-x4Tay1Zr1-y1O3 or its isomorphous heteroatom-doped compounds, Li with perovskite structure 3-2 x5Mx5Ha l O, Li3OCl or its isomorphous heteroatom-doped compounds, 2Li4-x6Si1-x6Px6O4 with LISICON structure or its isomorphous heteroatom-doped compounds, Li 14 ZnGe4O 16 or its isomorphous heteroatom-doped compounds, Li7-x7La3Zr2-x7O with garnet structure 12 or its isomorphous heteroatom-doped compounds, where 0 < x1 ≤ 0.75, 0 < x2 ≤ 0.5, 0.06 ≤ x3 ≤ 0.14, 0.25 ≤ y1 ≤ 1, x4 = 0.75y1, 0 ≤ x5 ≤ 0.01, 0.5 ≤ x6 ≤ 0.6; 0 ≤ x7 < 1; where M includes Mg 2+ 、Ca 2 + 、Sr 2+ or Ba 2+ in any one or a combination of at least two, and Hal is the element Cl or I.

[0084] The in-situ curing method of placing the raw materials in the battery includes:

[0085] (1) Placing the raw materials in the battery cell, which includes:

[0086] The raw materials and initiator are added to the electrolyte, and a solid-state battery with integrated cells is formed by in-situ curing; or at least one of the raw materials is pre-placed in a battery assembly, the initiator and the remaining raw materials are added to the electrolyte, and then injected into the prepared cell, and a solid-state battery with integrated cells is formed by in-situ curing;

[0087] (2) placing the raw material in a battery assembly of the battery, which comprises:

[0088] The raw materials are prepared into a precursor solution and coated on an electrode sheet, a diaphragm or a separate film, and in-situ cured to form an electrode sheet, a diaphragm or an electrolyte membrane with a polymer material coating; or the raw materials are mixed with positive and negative electrode slurries and in-situ cured to form a pole sheet containing a polymer material.

[0089] Among them, when the raw materials include raw material A and raw material B, the molar ratio of raw material B to raw material A is 0 to 1, such as 0, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc., and the total mass of raw material A and raw material B accounts for 1% to 80% of the total mass of the precursor solution, preferably 10% to 60%, more preferably 20% to 50%, such as 25%, 30%, 40%, 50%, etc.

[0090] Under a humidity condition with a dew point lower than -45°C, lithium salt, additive, organic solvent, raw material A, raw material B and initiator are uniformly mixed to obtain a precursor solution.

[0091] The mass fraction of the lithium salt in the precursor solution is 5% to 30%, preferably 10% to 25%, and more preferably 15% to 20%.

[0092] The organic solvent is one or more combinations of ethylene carbonate, fluoroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl formate, ethyl formate, propyl formate, butyl formate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, δ-valerolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 2-methyl-1,3-dioxolane, ethylene glycol dimethyl ether, polyethylene glycol, cyclopentane, triethylene glycol dimethyl ether, fluorinated 1,4-dimethoxybutane, bis(2,2,2-trifluoroethyl) ether, tetramethylsilane, and tetraethylene glycol dimethyl ether.

[0093] The mass fraction of the organic solvent in the precursor solution is 1% to 90%, preferably 10% to 80%, more preferably 20% to 60%, such as 30%, 40%, 50%, etc.

[0094] The initiator is one or more combinations of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), dimethyl azobisisobutyrate (AIBME), dibenzoyl peroxide (BPO), tert-butyl perbenzoate (BPB), methyl ethyl ketone peroxide or a composite initiator system (such as AIBN-ABVN or BPO-BPB, etc.).

[0095] The mass fraction of the initiator in the precursor solution is 0.001% to 0.5%, preferably 0.005% to 0.3%, more preferably 0.01% to 0.2%, such as 0.015%, 0.05%, 0.1%, 0.15%, etc.

[0096] The additives include one or more combinations of fluoroethylene carbonate, vinylene carbonate, trimethyl phosphate, triethyl phosphate, succinic anhydride, 18-crown ether-6, triphenyl phosphite, vinyl ethylene carbonate, trimethyl borate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, tributyl phosphate, biphenyl, vinyl sulfite, difluorodiphenylsilane, lithium bisfluorosulfonyl imide, tributyl borate, ethoxypentafluorocyclotriphosphazene, vinyl sulfate, lithium nitrate, 1,3-propane sultone, lithium difluorophosphate, diethyl sulfite, and succinonitrile.

[0097] In practical applications, the electrolyte may be an existing commercial electrolyte for lithium secondary batteries, or may be independently prepared. The present invention has no particular limitation on its composition and ratio.

[0098] Technical effect:

[0099] The present application innovatively provides a polymer material containing phosphorus groups, which can be flexibly applied in batteries to improve battery safety, improve battery ion transmission, improve battery cycle stability, and extend battery service life.

[0100] The polymer material provided in the present application contains a special structure as shown in Formula 1, and the solid-state battery prepared by the non-in-situ curing or in-situ curing method greatly improves the safety and cycle stability of the battery.

[0101] In addition, the in-situ curing method can greatly improve the interface contact between the battery material (such as electrolyte) and the pole piece, reduce polarization and interface impedance, thereby improving the battery's energy density, cycle times and other electrical properties, greatly improving the battery's electrochemical performance and extending the battery's service life. The in-situ curing preparation process is simple, safe and environmentally friendly, greatly reducing the use and emission of organic solvents, and is compatible with existing liquid battery processes, making it easy to quickly promote industrialization. Compared with non-in-situ curing processes, in-situ curing processes can better improve battery safety and electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0102] Figure 1 It is a comparison chart of battery cycle curves of Experimental Example 1 of the present application;

[0103] Figure 2 This is a comparison chart of the battery puncture test results of Experimental Example 2 of the present application. DETAILED DESCRIPTION

[0104] The specific implementation of the present application is described below in conjunction with the accompanying drawings.

[0105] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields. At the same time, in order to better understand the present invention, the definitions and explanations of the relevant terms are provided below.

[0106] In the embodiments of the present application, the polymerization degrees p and n of the polymer units in the polymer material structure can be calculated using the number average molecular weight method.

[0107] The number-average molecular weight is the most commonly used method for calculating the degree of polymerization. Polymer materials are composed of polymer units with the same chemical composition but different degrees of polymerization. The number-average molecular weight (Mn) can be obtained by averaging the number of molecules. Number-average molecular weight = sum of molecular weights of each component * number of moles of component / total number of moles. The calculation formula of number-average molecular weight is prior art and will not be described in detail here.

[0108] In this example, the H NMR spectrum 1 In H NMR, s represents a singlet, d represents a doublet, t represents a triplet, q represents a quartet, m represents a multiplet (multiplet greater than four, such as a quintet, sextet, etc.), dd represents a doublet, and dt represents a doublet; the number before the bracket represents the chemical shift, and the number before H in the bracket represents the number of H, such as 2.22 (s, 2H), which means that there are two Hs with a chemical shift of 2.22, and the peak is a singlet. Other situations can be deduced by analogy and will not be repeated.

[0109] In this example, MS (ESI) m / z …… (MH) + Represents mass spectrum.

[0110] In the embodiments of the present application, the corresponding substances of the English abbreviations are as follows: ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethylene carbonate (EC); lithium nitrate (LiNO3), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), lithium tetrafluorooxalate phosphate (LiPC2O2F4), 1,4-dimethoxybutane fluoride (FDMB), 1,3-propane sultone (1,3-PS), lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC); lithium difluorooxalatoborate (LiODFB), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium bis(fluoromethylsulfonyl)imide (LiFSI); azobisisobutyronitrile (AIBN), dibenzoyl peroxide (BPO).

[0111] In the embodiments of the present application, 0.1C / 0.1C means charging at a rate of 0.1C and discharging at a rate of 0.1C; 0.5C / 0.5C means charging at a rate of 0.5C and discharging at a rate of 0.5C.

[0112] In the present application, the polymer material may be placed in a battery component or a battery cell of the battery, and the battery may be prepared by an ex-situ curing process;

[0113] Or the raw materials for preparing the polymer material are placed in the battery assembly or battery core of the battery, and the battery is prepared by an in-situ curing process. Wherein, the battery assembly includes electrodes, a separator and an electrolyte membrane.

[0114] The non-in-situ curing method of placing the polymer material in the battery includes:

[0115] (1) placing the polymer material in the battery cell of the battery; specifically comprising: first adding the polymer material into an electrolyte to dissolve it, and then injecting it into the prepared battery cell;

[0116] (2) placing the polymer material in a battery assembly of the battery; specifically comprising:

[0117] The polymer material is dissolved in a solvent, and then coated on an electrode sheet, a diaphragm or formed into a separate film to form an electrode sheet, a diaphragm or an electrolyte membrane with a polymer material coating; or the polymer material is mixed in a positive and negative electrode slurry to form an electrode sheet containing the polymer material;

[0118] The in-situ curing method of placing the raw material in the battery includes:

[0119] (1) placing the raw materials in the battery cell of the battery; specifically including: adding the raw materials and the initiator into the electrolyte, and forming a solid-state battery with an integrated battery cell through in-situ curing; or pre-placing at least one of the raw materials in the battery assembly, adding the initiator and the remaining raw materials into the electrolyte, and then injecting them into the prepared battery cell, and forming a solid-state battery with an integrated battery cell through in-situ curing.

[0120] (2) placing the raw material in a battery assembly of the battery; specifically comprising:

[0121] The raw materials are prepared into a precursor solution and coated on an electrode sheet, a diaphragm or a separate film, and in-situ cured to form an electrode sheet, a diaphragm or an electrolyte membrane with a polymer material coating; or the raw materials are mixed with positive and negative electrode slurries and in-situ cured to form a pole sheet containing a polymer material.

[0122] It should be noted that the application methods shown in the following embodiments are only preferred application methods for the raw materials / battery materials, and other in-situ curing or non-in-situ curing application methods are also applicable.

[0123] Example 1

[0124] Ingredients A1: Ingredients B1:

[0125] Preparation method: 0.02 mol 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 0.02 mol glycidyl methacrylate (GMA) and 25 ml xylene were mixed, added into a 50 ml three-necked flask, stirred at 130° C. for 72 hours, cooled, and then 0.02 mol butyl lithium was added to react, and then the solvent was removed by reduced pressure distillation at 60° C. to obtain raw material A1.

[0126] 0.05 mol of ethanolamine hydrochloride (CAS: 2002-24-6) was added to 30 mL of toluene, and after heating to 110°C, 0.06 mol of methacryloyl chloride (CAS: 920-46-7) was slowly added within 15 min, and the mixture was stirred at 110°C for 4 h. The reaction solution was then cooled to 0°C in an ice-water bath, and the precipitate was filtered through a glass yarn funnel, washed with isopropyl ether, and dried in a vacuum drying oven to obtain 2-aminoethyl methacrylate hydrochloride. (CAS: 2420-94-2); 0.02 mol of 2-aminoethyl methacrylate hydrochloride was added to 8 ml of toluene, heated to 85°C, and then 5.9 g of bis(trichloromethyl) carbonate was added. After the temperature was kept constant for 3 hours, the reaction solution was subjected to rotary evaporation to remove the toluene solvent to obtain 2-isocyanatoethyl methacrylate. (CAS: 30674-80-7); 0.012 mol of 2-isocyanatoethyl methacrylate and 0.010 mol of 5-hydroxy-2,6-norbornane sultone (CAS: 15486-54-1), added to 25 ml of dichloromethane, stirred for 3 hours, added dropwise a dichloromethane solution containing 0.02 g of stannous isooctanoate through a constant pressure funnel, reacted at 10°C for 5 hours, then rotary evaporated at 25°C to remove the solvent to obtain raw material B1.

[0127] H NMR spectrum of raw material A1 1 H NMR (300MHz, DMSO, δppm): 7.47 (d, 1H), 8.00 (d, 1H), 7.43 (d, 1H), 7.75 (d, 1H), 7.41 (d, 1H), 7.36 (d, 1H), 7.50 (d, 1H), 7.29 (d, 1H), 2.51 (dt, 1H), 2.56 (dt, 1H), 4.2 (m, 1H), 4.41 (m, 1H), 4.16 (m, 1H), 2.01 (s, 3H), 6.48 (s, 1H), 6.40 (s, 1H).

[0128] H NMR spectrum of raw material B1 1 H NMR (300MHz, DMSO, δppm): 6.76 (s, 1H), 2.84 (q, 1H), 5.23 (t, 1H), 4.65 (dd, 1H), 1.60 (m, 1H), 2.62 (m, 1H), 1.91 ( m, 1H), 1.65 (m, 1H), 2.13 (m, 1H), 1.88 (m, 1H), 4.58 (m, 2H), 3.15 (t, 2H), 2.01 (s, 3H), 6.48 (s, 1H), 6.40 (s, 1H).

[0129] Application method: Add raw materials A1, B1 and initiator into the electrolyte to prepare a precursor solution, and then inject the precursor solution into the battery cell for in-situ curing.

[0130] The raw material A1 and the raw material B1 are copolymerized to form a 100 H A1 Polymerization unit and 10 H B1 The polymer material is composed of polymer units, and the structure of the polymer material is mainly based on three H A1 Polymerization unit H B1 The polymer units are arranged in an alternating manner.

[0131] Among them, H A1 The structure of the polymer unit is -Q1 is -CH3, -Q2 is m is 1 and p is 100.

[0132] H B1 The structure of the polymer unit is -Q3 is -CH3, -Q4 is n is 10.

[0133] It should be noted that the performance of polymer materials containing heteroatoms in their structure is better. Preferably, the P atom is connected to the C atom rather than directly to the heteroatom, so that a certain distance can be maintained between the phosphorus group and the heteroatom. This can better promote the role of the phosphorus group and help improve the safety of the polymer material.

[0134] Example 2

[0135] Ingredients A2: Raw materials B2:

[0136] Preparation method: by and Raw material A2 was obtained by acid catalysis reaction. The preparation method of raw material B2 is shown in Example 1. Raw material A2: MS (ESI) m / z 430.12 (MH) + ; Raw material B2: MS (ESI) m / z 345.09 (MH) + .

[0137] Application method: Add raw materials A2, B2 and initiator into the electrolyte to prepare a precursor solution, and then inject the precursor solution into the battery cell for in-situ curing.

[0138] The raw material A2 and the raw material B2 are copolymerized to form a 500 H A2 Aggregation unit and 150 H B2 A polymer material composed of polymer units, the structure of which is mainly arranged in a block manner.

[0139] Among them, H A2 The structure of the polymer unit is -Q1 is -CH3, -Q2 is m is 1 and p is 500.

[0140] H B2 The structure of the polymer unit is -Q3 is none, -Q4 is n is 150.

[0141] Example 3

[0142] Raw Materials A3: Raw material B3:

[0143] Preparation method: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and The reaction can produce raw material A3. The specific preparation steps can be referred to Example 1. Since the preparation method of the raw material is not within the scope of protection of this application, it will not be repeated. Raw material A3: MS (ESI) m / z 314.11 (MH) + .

[0144] 2-Isocyanatoethyl methacrylate, 0.020 mol 2-isocyanatoethyl methacrylate and 0.020 mol 4-hydroxyethylene sulfate were added to 20 ml chloroform, stirred for 2 hours, and a chloroform solution containing 0.009 g 1,4-diazabicyclo[2.2.2]octane was added dropwise through a constant pressure funnel, reacted at 5°C for 8 hours, and then the solvent was removed by rotary evaporation at 50°C to obtain raw material B3. Raw material B3: MS (ESI) m / z 295.04 (MH) + .

[0145] Application method: Add raw materials A3, B3 and initiator into the electrolyte to prepare a precursor solution, and then inject the precursor solution into the battery cell for in-situ curing.

[0146] The raw material A3 and the raw material B3 are copolymerized to form a 10000 H A3 Aggregation unit and 100 H B3 A polymer material composed of polymer units, the structure of which is mainly randomly arranged.

[0147] Among them, H A3 The structure of the polymer unit is -Q1 is none, -Q2 is m is 1 and p is 10000.

[0148] H B3 The structure of the polymer unit is -Q3 is -CH3, -Q4 is n is 100.

[0149] Example 4

[0150] Raw Materials A4: Raw material B4:

[0151] Preparation method: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and The reaction yields raw material A4. The specific preparation steps can be found in Example 1. Since the preparation method of the raw material is not within the scope of protection of this application, it will not be described in detail. Raw material B4 is an existing compound and can be purchased directly.

[0152] H NMR spectrum of raw material A4 1 H NMR (300MHz, DMSO, δppm): 5.73 (s, 1H), 7.47 (d, 1H), 8.00 (d, 1H), 7.43 (d, 1H), 7.75 (d, 1H), 7.41 (d, 1H), 7.36 (d , 1H), 7.50(d, 1H), 7.29(d, 1H), 2.88(dt, 1H), 2.63(dt, 1H), 4.3(q, 1H), 5.89(m, 1H), 5.28(d, 1H), 5.29(s, 1H).

[0153] H NMR spectrum of raw material B4 1 H NMR (300MHz, DMSO, δppm): 4.55 (t, 2H), 5.93 (m, 1H), 5.38 (d, 1H), 5.26 (d, 1H).

[0154] Application method: Add raw materials A4, B4 and initiator into the electrolyte to prepare a precursor solution, and then inject the precursor solution into the battery cell for in-situ curing.

[0155] The raw material A4 and the raw material B4 are copolymerized to form a 4000 H A4 Aggregation unit and 800 H B4 A polymer material composed of polymer units, wherein H A4 , H B4 Mainly arranged according to period, (H A4 -H A4 -H A4 -H A4 -H A4 -H B4 ) is a cycle.

[0156] Among them, H A4 The structure of the polymer unit is -Q1 is none, -Q2 is m is 1 and p is 4000.

[0157] H B4 The structure of the polymer unit is -Q3 is none, -Q4 is n is 800.

[0158] Example 5

[0159] Raw material A5: Raw material B5:

[0160] Preparation method: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and The reaction yielded the raw material A5. The specific preparation steps can be found in Example 1. Since the preparation method of the raw material is not within the scope of protection of this application, it will not be described in detail. Raw material A5: MS (ESI) m / z 300.09 (MH) + .

[0161] Dissolve 0.02 mol of vinyl phosphate in 20 ml of water, stir thoroughly, add 0.04 mol of lithium hydroxide, react at 25°C for 2 hours, remove water by vacuum distillation at 60°C, and dry to obtain raw material B5. Raw material B5: MS (ESI) m / z 132.00 (MH) + .

[0162] Application method: Pre-place raw material A5 at the positive electrode, add initiator and raw material B5 into the electrolyte and then inject it into the prepared battery cell for in-situ curing.

[0163] The raw material A5 and the raw material B5 are copolymerized to form a 2000 H A5 Aggregation unit and 1000 H B5 A polymer material composed of polymer units, wherein H A5 , H B5 Mainly arranged in gradient, 40 H A5 -40 H B5 -20 H A5 -20 H B5 -10 H A5 -10 H A5 -8 H A5 -8 H A5 …….

[0164] Among them, H A5 The structure of the polymer unit is -Q1 is -CH3, -Q2 is m is 1 and p is 2000.

[0165] H B5 The structure of the polymer unit is -Q3 is none, -Q4 is n is 1000.

[0166] Example 6

[0167] Ingredients A6: Raw material B6:

[0168] Preparation method: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and The reaction yields the raw material A6. The specific preparation steps can be found in Example 1. Since the preparation method of the raw material is not within the scope of protection of this application, it will not be described in detail.

[0169] 0.01 mol of 5,5-difluoro-4-hydroxy-1,3-dioxolane-2-one, 0.011 mol of acrylic acid and 25 ml of toluene were mixed and added into a 50 ml three-necked flask. After sufficient stirring, the temperature was raised to 100°C, and then 0.0216 g of a toluene solution of methylimidazole was added. The mixture was reacted at 105°C for 5 hours, and then the solvent was removed by reduced pressure distillation at 100°C to obtain a polymerizable monomer B6.

[0170] Raw material A6: MS (ESI) m / z 340.12 (MH) + ; Raw material B6: MS (ESI) m / z 176.01 (MH) + .

[0171] Application method: pre-place raw material A6 on the diaphragm, add initiator and raw material B5 into the electrolyte and then inject into the prepared battery cell for in-situ curing.

[0172] The raw material A6 and the raw material B6 are copolymerized to form a 100 H A6 Aggregation unit and 60 H B6 A polymer material composed of polymer units, wherein H A6 , H B6 Mainly arranged randomly.

[0173] Among them, H A6 The structure of the polymer unit is -Q1 is none, -Q2 is m is 1 and p is 100.

[0174] H B6 The structure of the polymer unit is -Q3 is none, -Q4 is n is 60.

[0175] Example 7

[0176] Raw materials A7: Ingredients B7:

[0177] Preparation method: by The raw material A7 was obtained by acid catalysis. Raw material A7: MS (ESI) m / z 314.11 (MH) + ; Raw material B7 is the existing structure, Raw material B7: MS (ESI) m / z 146.04 (MH) + .

[0178] Application method: Add raw materials A7 and B7 and initiator to the positive electrode slurry, mix them evenly and apply them on aluminum foil, solidify them in situ at 50°C for 6 hours to form a positive electrode sheet with battery materials.

[0179] The raw material A7 and the raw material B7 are copolymerized to form a 10H A7 Polymerization unit and 10 H B7 A polymer material composed of polymer units, wherein H A7 , H B7 Mainly irregular arrangement.

[0180] Among them, H A7 The structure of the polymer unit is -Q1 is -CH3, -Q2 is m is 1 and p is 10.

[0181] H B7 The structure of the polymer unit is -Q3 is none, -Q4 is n is 10.

[0182] Example 8

[0183] Raw Materials A8: Raw materials B8:

[0184] Preparation method: by PCl3 was reacted at 150°C for 5 h under the catalysis of trifluoromethanesulfonic acid, and then deionized water was added after the temperature dropped to room temperature to obtain Will Add Et3N to HCCl3 solvent and react at 0℃ for 3 hours to obtain Then Hexamethyldisilazane and a base catalyst are added to tetrahydrofuran solvent and reacted at 20° C. to obtain raw material A8.

[0185] H NMR spectrum of raw material A8 1 H NMR (300MHz, DMSO, δppm): 8.41 (s, 1H), 8.97 (d, 1H), 8.52 (s, 1H), 7.47 (d, 1H), 7.75 (d, 1H), 8.00 (d, 1H), 7.50(d, 1H), 7.29(t, 1H), 2.82(m, 2H), 3.50(t, 2H), 6.48(dd, 1H), 6.09(dd, 1H), 5.74(dd, 1H).

[0186] Will Stannous isooctanoate is added to CH2Cl2 solvent and reacted at 20°C to obtain raw material B8.

[0187] H NMR spectrum of raw material B8 1 H NMR (300MHz, DMSO, δppm): 8.25 (s, 1H), 4.04 (d, 2H), 5.84 (m, 1H), 5.19 (d, 1H), 5.06 (d, 1H).

[0188] Application method: The raw materials A8 and B8 are prepared into a precursor solution, which is coated on the surface of the positive electrode, and in-situ cured to form a positive electrode with the polymer material coating.

[0189] The raw material A8 and the raw material B8 are copolymerized to form a 20H A8 Polymerization unit and 5 H B8 A polymer material composed of polymer units, wherein H A8 , H B8 Mainly according to the four H A8 Polymerization unit H B8 The polymer units are arranged in an alternating manner.

[0190] Among them, H A8 The structure of the polymer unit is -Q1 is none, -Q2 is m is 1 and p is 20.

[0191] H B8 The structure of the polymer unit is -Q3 is none, -Q4 is n is 5.

[0192] Example 9

[0193] Raw materials A9: Raw materials B9:

[0194] Preparation method: Add NaBH4 to dioxane solvent and react at 90℃ for 6h to obtain pass Reaction acquisition (Reaction conditions refer to the following literature, DOI: 10.1016 / j.tetlet.2015.02.003), Add lithium ethoxide to isopropanol solvent and react at 120°C for 72h to obtain raw material A9. Raw material A9: MS (ESI) m / z 320.12 (MH) + .

[0195] Will Reaction with Br2 and H2O at 90℃ for 6h to obtain Will Add diethylaminosulfur trifluoride to CH2Cl2 solvent and react at 0℃ for 1h to obtain Will Add Mg to ether solvent and react at 25℃ for 2h to obtain Grignard reagent Will Add sodium ethoxide to ether solvent and react at 25°C for 3h to obtain pass React with 67% concentrated sulfuric acid aqueous solution at 100°C for 2h to obtain raw material B9. Raw material B9: MS (ESI) m / z 180.03 (MH) + .

[0196] Application method: The raw materials A9 and B9 are prepared into a precursor solution, which is coated on the surface of the negative electrode, and in-situ cured to form a negative electrode with the polymer material coating.

[0197] The raw material A9 and the raw material B9 are copolymerized to form a 300 H A9 Aggregation units and 270 H B9 A polymer material composed of polymer units, wherein H A9 , H B9 Mainly irregular arrangement.

[0198] Among them, H A9 The structure of the polymer unit is -Q1 is none, -Q2 is m is 1 and p is 300.

[0199] H B9 The structure of the polymer unit is -Q3 is none, -Q4 is n is 270.

[0200] Example 10

[0201] Raw material A10: Raw material B10:

[0202] Raw materials A10 and B10 are existing substances. Raw material A10: MS (ESI) m / z 285.09 (MH) + ; Raw material B10: MS (ESI) m / z 138.02 (MH) + .

[0203] Application method: Add raw materials A10, B10 and initiator into the electrolyte to prepare a precursor solution, and then inject the precursor solution into the battery cell for in-situ curing.

[0204] The raw material A10 and the raw material B10 are copolymerized to form a 8000 H A10 Aggregation unit and 400 H B10 A polymer material composed of polymer units, wherein H A10 , H B10 Mainly irregular arrangement.

[0205] Among them, H A10 The structure of the polymer unit is -Q1 is none, -Q2 is m is 1 and p is 8000.

[0206] H B10 The structure of the polymer unit is -Q3 is none, -Q4 is n is 400.

[0207] Embodiment 11

[0208] Raw material A11: Ingredients B11:

[0209] Preparation method: Raw materials A11 and B11 are existing substances. Raw material A11: MS (ESI) m / z 270.08 (MH) + ; Raw material B11: MS (ESI) m / z 148.02 (MH) + .

[0210] Application method: Prepare the raw materials A11 and B11 into a precursor liquid, apply it on the surface of the diaphragm, and solidify it in situ to form a diaphragm with the polymer material coating.

[0211] The raw material A11 and the raw material B11 are copolymerized to form a 200 H A11 Aggregation unit and 140 H B11 A polymer material composed of polymer units, wherein H A11 , H B11 Mainly block arrangement.

[0212] Among them, H A11 The structure of the polymer unit is -Q1 is -CH3, -Q2 is m is 1 and p is 200.

[0213] H B11 The structure of the polymer unit is -Q3 is none, -Q4 is n is 140.

[0214] Example 12

[0215] Raw Materials A12: Raw material B12:

[0216] Raw material A12 is an existing substance, CAS: 1093943-00-0 Raw material A12: MS (ESI) m / z 300.09 (MH) + ; Raw material B12 is an existing substance: MS (ESI) m / z 142.00 (MH) + .

[0217] Application method: Add raw materials A12, B12 and initiator into the electrolyte to prepare a precursor solution, and then inject the precursor solution into the battery cell for in-situ curing.

[0218] The raw material A12 and the raw material B12 are copolymerized to form a 300 H A12 Aggregation unit and 240 H B12 A polymer material composed of polymer units, wherein H A12 , H B12 Mainly block arrangement.

[0219] Among them, H A12 The structure of the polymer unit is -Q1 is -CH2-OH, -Q2 is m is 1 and p is 300.

[0220] H B12 The structure of the polymer unit is -Q3 is none, -Q4 is n is 240.

[0221] Embodiment 13

[0222] Polymer Material G1:

[0223] Application method: first prepare the polymer material G1, then mix the polymer material G1 into the negative electrode slurry, and coat it on the aluminum foil to obtain the negative electrode containing the polymer material G1, stack and bake the positive electrode sheet, the negative electrode sheet and the separator to obtain a dry battery cell, and then inject the electrolyte, package the battery, and let it stand at room temperature for 12 hours to allow the battery cell to be fully soaked to obtain a solid-state battery containing the polymer material G1.

[0224] Embodiment 14

[0225] Polymer Material G2: MS (ESI) m / z 4185.38 (MH) +

[0226] Application method: first prepare the polymer material G2, then add the polymer material G2 into the electrolyte to dissolve it, to obtain the electrolyte containing the battery material, then stack and bake the positive electrode sheet, the negative electrode sheet and the separator to obtain a dry battery cell, after the electrolyte is injected into the battery cell, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked, to obtain a solid-state battery containing the polymer material G2.

[0227] Embodiment 15

[0228] Polymer Material G3: MS (ESI) m / z 4251.88 (MH) +

[0229] The nuclear magnetic resonance hydrogen spectrum of polymer material G3 is as follows: G3 1 H NMR (300MHz, DMSO, δppm): 4.77(s, 8H), 9.24(s, 8H), 9.25(s, 8H), 8.44(d, 8H), 8.29(d, 8H), 7.52(d, 8H), 7.24(d , 8H), 2.81 (m, 16H), 3.80 (t, 8H), 3.5 (m, 8H), 3.30 (s, 3H), 2.05 (q, 14H), 1.86 (q, 2H), 1.55 (t, 16H), 1.20 (s, 3H).

[0230] Application method: first prepare the polymer material G3, then mix the polymer material G3 into the negative electrode slurry, and coat it on aluminum foil to obtain a negative electrode containing the polymer material G3. The positive electrode sheet, the negative electrode sheet and the separator are stacked and baked to obtain a dry battery cell. Then, the electrolyte is injected, the battery is packaged, and it is allowed to stand at room temperature for 12 hours to allow the battery cell to be fully soaked to obtain a solid-state battery containing the polymer material G3.

[0231] Example 16

[0232] Polymer Material G4: MS (ESI) m / z 22852.56 (MH) +

[0233] Application method: first prepare the polymer material G4, then add the polymer material G4 into the electrolyte to dissolve it, to obtain the electrolyte containing the battery material, then stack and bake the positive electrode sheet, the negative electrode sheet and the separator to obtain a dry battery cell, after the electrolyte is injected into the battery cell, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked, to obtain a solid-state battery containing the polymer material G4.

[0234] Test Example 1

[0235] 1. Preparation of positive electrode sheet

[0236] The positive electrode active material, conductive agent, binder, and fast ion conductor are mixed uniformly according to the data ratios listed in Table 1C1-C6 to obtain a positive electrode slurry with a certain fluidity; then, the slurry is coated on an aluminum foil, and the surface capacity of the electrode is controlled to be 4 mAh / cm 2 , blast drying, and roller pressing, the obtained positive electrode sheets are named C1, C2...C6. Among them, the conductive agent is carbon nanotubes and conductive carbon black (CNT+Super-P, the mass ratio of the two is 1:2), and the binder is polyvinylidene fluoride (PVDF). The ratio is the mass ratio of the positive electrode main material, the binder, the conductive agent, and the fast ion conductor.

[0237] The positive electrode material is LiCoO2 (abbreviated as LCO), LiNi 0.83 Co 0.12 Mn 0.05 O2 (abbreviated as Ni83), LiNi 0.88 Co 0.09 Mn 0.03 O2 (abbreviated as Ni88), LiNi 0.8 Co 0.15 Al 0.05 O2 (abbreviated as NCA). The fast ion conductor is Li 1.4 Al 0.4 Ti 1.6 (PO4)3 (abbreviated as LATP), Li 6.4 LqCy 1.6 Ta 0.6 O 12 (abbreviated as LLZO).

[0238] Table 1 Positive electrode sheet

[0239]

[0240]

[0241] 2. Preparation of negative electrode sheet

[0242] The negative electrode main material active material, conductive agent, and binder are added to deionized water according to the data listed in Table 2 and mixed and stirred evenly to obtain a negative electrode slurry with a certain fluidity; then, it is coated on copper foil, and the control electrode surface capacity is 4.2 mAh / cm 2 Blast drying and roller pressing are performed to obtain negative electrode sheets or metal lithium is directly used as the negative electrode, which are named F1, F2, ... F4 respectively. The ratio is the mass ratio of the negative electrode main material, the binder, and the conductive agent.

[0243] serial number negative electrode Conductive agent Binder Proportion F1 Silicon Oxygen Carbon CNT+Super-P CMC+SBR 95:2:3 F2 Natural graphite CNT+Super-P CMC+SBR 95:2:3 F3 Silicon Carbon CNT+Super-P CMC+SBR 95:2:3 F4 Lithium Metal —— —— ——

[0244] Table 2 Negative electrode

[0245] The silicon-carbon material uses the SL450A-SOC nano silicon-carbon negative electrode material of Liyang Tianmu Pioneer Battery Material Technology Co., Ltd., and the silicon-oxygen-carbon material is the S450-2A silicon-oxygen-carbon negative electrode material of Beite New Energy Materials Co., Ltd.; the binder is sodium carboxymethyl cellulose and styrene-butadiene rubber (CMC+SBR).

[0246] 3. Diaphragm

[0247] Table 3 Diaphragm

[0248] serial number Diaphragm Specification / μm S1 PP double-sided ceramic 2+12+2 (12-substrate 2-alumina ceramic) S2 PE double-sided ceramic 2+9+2 (9-substrate 2-alumina ceramic)

[0249] 4. Electrolyte

[0250] In practical applications, the electrolyte may be an existing commercial electrolyte for lithium secondary batteries, or may be independently prepared. The present invention has no particular limitation on its composition and ratio.

[0251] Table 4 Electrolyte configuration

[0252]

[0253] 5. Battery Assembly

[0254] Preparation of Battery 1-Battery 4, Battery 10, Battery 12, Comparative Batteries 1-4, and Comparative Batteries 7-13

[0255] According to the data listed in Table 5, in an environment with a dew point below -45°C, the precursor solution is injected into the battery cell and left to stand for 6-12 hours, and then cured at 50-60°C for 6-8 hours to obtain an in-situ polymerized electrolyte. Then, the in-situ cured battery is obtained through formation, secondary sealing, and capacity separation processes.

[0256] Preparation of Battery 5 and Comparative Battery 5

[0257] The raw material A5 is pre-placed in the positive electrode plate. First, the raw material A5 is added to the slurry of the positive electrode C3 and mixed evenly, and then coated on the aluminum foil to obtain the positive electrode plate containing the raw material A5. The positive electrode plate, the negative electrode plate and the separator are stacked and baked to obtain a dry battery cell. Then, B5 and the initiator or a single initiator are added to the electrolyte, injected into the prepared battery cell for in-situ curing to obtain a solid-state battery containing a polymer material.

[0258] Preparation of Battery 6 and Comparative Battery 6

[0259] The raw material A6 is pre-placed on the diaphragm. First, the raw material A6 is prepared into a slurry and coated on the surface of the diaphragm. The coating thickness is controlled to be 3 μm. The positive electrode sheet, the negative electrode sheet and the diaphragm containing the raw material A6 are stacked and baked to obtain a dry battery cell. Then, B6 and an initiator or a single initiator are added to the electrolyte and injected into the prepared battery cell for in-situ curing to obtain a solid-state battery containing a polymer material.

[0260] Preparation of Battery 7

[0261] According to the data listed in Table 5, raw materials A7, B7 (the molar ratio of B7 to A7 is 0.5) and initiator AIBN are mixed into the slurry for preparing positive electrode C4 and mixed evenly, coated on aluminum foil and then thermally induced in-situ cured to obtain a positive electrode sheet containing battery materials, the positive electrode sheet containing battery materials, the negative electrode sheet A2 and the separator S2 are stacked and baked to obtain a dry battery cell, and then the electrolyte E4 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully wetted to obtain a solid-state battery containing battery materials.

[0262] Preparation of Battery 8

[0263] According to the data listed in Table 5, raw materials A8, B8 (the molar ratio of B8 to A8 is 0.25) and initiator AIBN are added to the solvent, mixed evenly to obtain a raw material solution containing the polymer material raw material, which is applied to the surface of the positive electrode C5, and the coating thickness is controlled to be 2 μm. The monomer is then in situ polymerized at 50°C to obtain a positive electrode sheet containing a polymer material coating. The positive electrode sheet containing the polymer material coating, the negative electrode sheet F2 and the separator S1 are stacked and baked to obtain a dry battery cell, and then the electrolyte E4 is injected, the battery is packaged, and the battery is left standing at room temperature for 12 hours to allow the battery cell to be fully wetted to obtain a solid-state battery containing battery materials.

[0264] Preparation of Battery 9

[0265] According to the data listed in Table 5, raw materials A9, B9 (the molar ratio of B9 to A9 is 0.9) and initiator BPO are added to the solvent, mixed evenly to obtain a raw material solution containing a polymer material raw material, which is applied to the surface of the negative electrode F1, and the coating thickness is controlled to be 2 μm. The monomer is then in-situ polymerized at 50°C to obtain a negative electrode sheet containing a polymer material coating. The positive electrode sheet C6, the negative electrode sheet containing a polymer material coating and the separator S1 are stacked and baked to obtain a dry battery cell, and then the electrolyte E5 is injected, the battery is packaged, and the battery is left standing at room temperature for 12 hours to allow the battery cell to be fully infiltrated to obtain a solid-state battery containing battery materials.

[0266] Preparation of Battery 11

[0267] According to the data listed in Table 5, raw materials A11, B11 (the molar ratio of B11 to A11 is 0.7) and initiator BPO are added to the solvent, mixed evenly to obtain a raw material solution containing polymer material raw materials, which is applied to the surface of the diaphragm S2, and the coating thickness is controlled to be 2 μm. The monomer is then in situ polymerized at 50°C to obtain a diaphragm containing a polymer material coating. The positive electrode piece C5, the negative electrode piece F4 and the diaphragm containing a polymer material coating are stacked and baked to obtain a dry battery cell, and then the electrolyte E6 is injected, the battery is packaged, and the battery is left to stand at room temperature for 12 hours to allow the battery cell to be fully wetted to obtain a solid-state battery containing battery materials.

[0268] Preparation of Battery 13 and Battery 15

[0269] First, prepare the polymer material, then mix the polymer material into the slurry for preparing the negative electrode F1 and mix evenly, and then coat it on aluminum foil to obtain a negative electrode sheet containing the polymer material. The positive electrode sheet C2, the negative electrode sheet containing the polymer material and the separator S1 are stacked and baked to obtain a dry battery cell, and then the electrolyte E2 added with the battery material is injected, the battery is packaged, and it is allowed to stand at room temperature for 12 hours to allow the battery cell to be fully infiltrated to obtain a solid-state battery containing the polymer material.

[0270] Preparation of Battery 14 and Battery 16

[0271] First, prepare the polymer material, then add the polymer material into the electrolyte E3 to dissolve it, and obtain the electrolyte containing the battery material. Then, stack and bake the positive electrode sheet, the negative electrode sheet and the separator to obtain a dry battery cell, inject the electrolyte containing the battery material, package the battery, and let it stand at room temperature for 12 hours to allow the battery cell to be fully soaked, so as to obtain a solid-state battery containing the polymer material.

[0272] Preparation of Comparative Batteries 14 and 15

[0273] According to the data listed in Table 5, in an environment with a dew point below -45°C, the raw material A1 / A1+B1 was added to the electrolyte E1, and the positive electrode sheets, negative electrode sheets and separators were stacked and baked to obtain a dry battery cell, the above-mentioned electrolyte was injected, the battery was packaged, and allowed to stand at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a battery containing the raw materials but without polymerization.

[0274] The amount of initiator added to the solid-state battery is 0.2% to 2% of the mass of raw materials A+B.

[0275] Table 5 Configuration and test method of the battery in the embodiment

[0276]

[0277]

[0278] Among them, the structure of D1 is: The structure of D2 is:

[0279] 7. Battery Test

[0280] After the secondary battery was completely cured in situ, the first-week discharge capacity, first-week efficiency, and 200-cycle capacity retention rate of the battery were tested at room temperature. The test voltage range was 2.75 to 4.2 V. The cycle mode was 0.1C / 0.1C for 2 weeks and 0.5C / 0.5C for 198 weeks (C represents the rate). The test results are shown in Table 6.

[0281] Table 6 Battery test results

[0282]

[0283]

[0284] The present invention provides a polymer material containing phosphorus groups. A solid-state battery prepared by an in-situ curing or non-in-situ curing method greatly improves the cycle stability and safety of the battery and prolongs the battery life.

[0285] It can be seen from Table 6 that in the solid-state battery system with high nickel ternary (Ni83, Ni88, NCA), lithium cobalt oxide as the positive electrode, and graphite, silicon carbon, silicon oxygen carbon, and metallic lithium as the negative electrode, compared with the conventional liquid battery, the energy density of the solid-state battery prepared by the present invention is only slightly reduced, but the cycle stability of the battery is significantly improved; the solid-state battery prepared by using raw material A+B and inducing in-situ curing (battery 1-12) and the solid-state battery prepared by first preparing polymer material G using raw material A+B and then preparing solid-state battery (battery 14, battery 16), the battery capacity is 10.5Ah~10.9Ah, and the capacity retention rate after 200 cycles is 9 2.32%~93.68%; the solid-state batteries prepared by only using raw material A and in-situ curing (comparison batteries 1-8) and the solid-state batteries prepared by first preparing polymer material G using raw material A (battery 13, battery 15), the battery capacity is between 10.0-10.3Ah, and the capacity retention rate after 200 cycles is 90.11%~91.78%; the capacity retention rate of battery 1-12, battery 14, and battery 16 after 200 cycles is higher than that of comparison battery 1-8, battery 13, and battery 15, indicating that the solid-state batteries prepared by simultaneously introducing the polymer generated by raw materials A+B have higher cycle stability. The solid-state batteries (comparative batteries 9-11) prepared using only the polymer generated from raw material B have a battery capacity between 9.6 and 9.9 Ah, and a capacity retention rate of 92.01% to 92.38% after 200 cycles; the capacity retention rate of comparative batteries 9-11 after 200 cycles is higher than that of comparative batteries 1-8, battery 13, and battery 15, indicating that the introduction of B in the present invention can improve the cycle stability of the battery. The solid-state batteries prepared using only raw material D (comparison batteries 12-13) have a battery capacity between 9.3-9.4Ah, and a capacity retention rate of 79.71% to 79.97% after 200 cycles; the batteries prepared using raw material A or raw material A+B but without initiating polymerization (comparison batteries 14-15) have a battery capacity between 9.7-9.8Ah, and a capacity retention rate of 90.01% to 90.13% after 200 cycles; and the blank batteries 1-5 have a battery capacity below 9.4Ah, and a capacity retention rate of 85.31% to 86.62% after 200 cycles.

[0286] Depend on Figure 1It can be seen that the capacity retention rate of battery 1 is much higher than that of comparison battery 12 and blank battery 1, indicating that the polymer material provided in this application is applied to the battery, which can significantly improve the cycle performance of the battery. The capacity retention rate of battery 1 is higher than that of comparison battery 1, indicating that the solid-state battery prepared by introducing the polymer generated by raw materials A+B at the same time has better cyclability than the solid-state battery prepared by the polymer generated by raw material A only. The capacity retention rate of battery 14 is slightly lower than that of battery 1, indicating that the solid-state battery prepared by in-situ curing has better electrochemical performance, because the solid-state battery prepared by the in-situ curing method greatly improves the interface contact between the electrolyte and the pole piece, reduces polarization and interface impedance, and thus obtains better electrical performance (such as energy density, first-week efficiency, and capacity retention).

[0287] As can be seen from batteries 1-14, the present invention is applicable to various application modes. The raw materials can be directly applied to the electrolyte, or the raw materials can be pre-placed in the battery assembly, or the raw materials can be mixed into the positive and negative electrode slurries or prepared into precursor liquids to be coated on the surfaces of electrodes and diaphragms. It is also possible to use raw materials to first prepare polymer materials and then apply them to batteries. The application modes shown in the above embodiments are only preferred application modes for the raw materials / battery materials, and other in-situ curing or non-in-situ curing application modes are also applicable.

[0288] Test Example 2

[0289] Battery safety performance test

[0290] The solid-state batteries 1-16, comparison batteries 1-15, and blank batteries 1-5 prepared above were subjected to needle puncture safety tests according to the safety requirements and test methods for power batteries for electric vehicles GB-T31485-2015 for lithium-ion batteries.

[0291] 1. Needle penetration test: The battery is charged at 1C constant current and constant voltage, with a cut-off current of 0.05C; a φ8mm high-temperature resistant steel needle is used to penetrate the battery plate at a speed of 25mm / s from a direction perpendicular to the battery plate. The penetration position should be close to the geometric center of the punctured surface, and the steel needle stays in the battery; observe for 1h, monitor the changes in the surface temperature of the battery cell during the process, and record whether the battery cell catches fire or explodes. The results are shown in Table 7.

[0292] Table 7 Battery acupuncture result record

[0293]

[0294]

[0295] The present invention provides a polymer material containing phosphorus groups. The polymer material containing phosphorus groups is introduced into a solid-state battery by an in-situ curing or non-in-situ curing method, thereby greatly improving the safety of the battery.

[0296] As shown in Table 7, the solid-state batteries (batteries 1-12, batteries 14, and batteries 16) prepared with polymers generated from raw materials A+B did not catch fire or explode during the puncture test, and the surface temperature of the battery cells during the puncture was 41.2-46.3°C, which improved the safety of the batteries; while the solid-state batteries (comparative batteries 1-8, batteries 13, and batteries 15) prepared with polymers generated from raw materials A only did not catch fire or explode during the puncture test, and the surface temperature of the battery cells during the puncture was 66.5-72.2°C. The surface temperatures of the batteries 1-12, batteries 14, and batteries 16 were slightly lower than those of comparative batteries 1-8, batteries 13, and batteries 15, indicating that the solid-state batteries prepared by simultaneously introducing polymers generated from raw materials A+B have higher safety. The solid-state batteries prepared only with the polymer generated by raw material B (comparison batteries 9-11) caught fire and exploded when punctured, and the surface temperature of the battery cell was 292.6-297.5°C during puncture. The solid-state batteries prepared only with raw material D (comparison batteries 12-13) caught fire and exploded when punctured, and the surface temperature of the battery cell was 623.1-632.4°C during puncture. The batteries prepared using raw materials A or A+B but without initiating polymerization (comparison batteries 14-15) caught fire and exploded when punctured, and the surface temperature of the battery cell was 489.7-496.4°C during puncture. The blank batteries 1-5 caught fire and exploded when punctured, and the surface temperature of the battery cell was 621.8-632.7°C during puncture.

[0297] from Figure 2 It can be seen more intuitively that the solid-state battery prepared by the polymer generated by raw material A or the polymer generated by the simultaneous introduction of raw materials A+B in the present invention remains in good condition after acupuncture, while the blank battery and the comparison battery 12 caught fire and exploded after the acupuncture test and were severely damaged. This shows that the polymer material provided in the present application is applied to solid-state batteries, which can significantly improve the safety performance of the batteries.

[0298] 2. Battery Thermal Shock Safety Test

[0299] The battery was charged at 1C constant current and constant voltage, with a cut-off current of 0.05C; heated at 180℃ for 2h: heating rate 5℃ / s, heated to 180℃ and kept warm for 2h, observed for 1h; and recorded whether the battery caught fire or exploded. If it passed, it failed. The changes in the surface temperature of the battery cell were monitored during the process. The test results are shown in Table 8.

[0300] Table 8 Battery thermal shock safety results record

[0301]

[0302] The present invention provides a polymer material containing phosphorus groups. The polymer material containing phosphorus groups is introduced into a solid-state battery by an in-situ curing or non-in-situ curing method, thereby greatly improving the safety of the battery.

[0303] As shown in Table 8, the solid-state batteries (batteries 1-12, batteries 14, and batteries 16) prepared with polymers generated from raw materials A+B did not catch fire or explode during the thermal shock test, and the surface temperature of the battery core was 181.2-183.7°C, which significantly improved the safety of the batteries; while the solid-state batteries (comparative batteries 1-8, batteries 13, and batteries 15) prepared with polymers generated from raw materials A only did not catch fire or explode during the thermal shock test, and the surface temperature of the battery core was 187.1-188.6°C. The surface temperatures of the batteries 1-12, batteries 14, and batteries 16 were slightly lower than those of comparative batteries 1-8, batteries 13, and batteries 15, indicating that the solid-state batteries prepared by simultaneously introducing polymers generated from raw materials A+B have higher safety. The solid-state batteries prepared only with the polymer generated by raw material B (comparison batteries 9-11) caught fire and exploded during the battery thermal shock test, and the surface temperature of the battery cell was 232.6-237.5°C, while the solid-state batteries prepared only with raw material D (comparison batteries 12-13) caught fire and exploded during the battery thermal shock test, and the surface temperature of the battery cell was 620.1-632.4°C; the batteries prepared using raw materials A or A+B but without initiating polymerization (comparison batteries 14-15) caught fire and exploded when punctured, and the surface temperature of the battery cell was 486.8-491.9°C during puncture, indicating that polymerization is required for the present invention to better improve the battery safety; while the blank batteries 1-5 caught fire and exploded during the battery thermal shock test, and the surface temperature of the battery cell was 597.8-624.6°C.

[0304] (3) Extrusion test: After fully charging the battery, place it in two planes and squeeze it perpendicular to the plate direction at a rate of 2 mm / s. Stop squeezing when the voltage reaches 0V or the battery deformation reaches 50%. The battery passes the squeezing test if it does not catch fire or explode during the squeezing process.

[0305] Table 9 Comparison of extrusion test results

[0306]

[0307]

[0308] The present invention provides a polymer material containing a phosphorus group, and a polymer material containing a phosphorus group is introduced into a solid-state battery by an in-situ curing method or a non-in-situ curing method, which greatly improves the safety of the battery. As shown in Table 9, solid-state batteries prepared by using polymers generated by raw material A or polymers generated by introducing raw materials A+B at the same time all passed the extrusion test, and solid-state batteries prepared by polymers generated only by raw material B, batteries containing raw material A or raw materials A and B at the same time but without polymerization, and solid-state batteries containing only D1 and D2 and blank batteries did not pass the extrusion test. It further shows that the present invention improves the safety of the battery.

[0309] This application introduces a polymer material containing phosphorus groups, and the solid-state battery prepared by in-situ curing or non-in-situ curing method greatly improves the safety of the battery. And the solid-state battery prepared by in-situ curing has better electrochemical performance, because the solid-state battery prepared by the in-situ curing method greatly improves the interface contact between the electrolyte and the pole piece, reduces polarization and interface impedance, and thus obtains better electrical performance.

[0310] In the puncture test, thermal shock safety test, and extrusion test, all solid-state batteries prepared by polymers generated by raw material A or polymers generated by introducing raw materials A+B simultaneously passed the extrusion test, and solid-state batteries prepared by polymerizing both raw materials A and B had better safety and better electrochemical performance. Solid-state batteries prepared by polymers generated only by raw material B, solid-state batteries containing only D1 and D2, and blank batteries all failed the safety test. This shows that the polymer material in this application, when used in batteries, can significantly improve the safety performance of batteries.

[0311] It should be noted that the raw material A in this patent, or the mixture of raw material A and raw material B, can also be directly used in combination with commercial electrolytes, and excellent results can still be obtained, indicating that the raw materials used to prepare the polymer materials in this application have good compatibility with various electrolytes.

[0312] In summary, the solid-state battery prepared by the present invention can not only significantly improve the battery safety performance, but also extremely well maintain the electrochemical performance of the battery, and is suitable for large-scale promotion and application.

[0313] In the present invention, only some structures are selected as representatives in the examples to illustrate the preparation method and effects of the present application, and other structures not listed have similar effects.

[0314] For example, the polymer units -[M1-M2]- constituting the polymer material G may also include: Etc.; The polymer units represented by R5 and / or R6 constituting the polymer material G may also include: Due to limited space, other polymer units can be deduced by analogy and are not listed here one by one. The polymer material structure composed of any combination of the above polymer units is within the protection scope of this application.

[0315] In the above structure, R is H, Li or BF3Li, A indicates that any position on the ring can be substituted by a halogen atom, an alkyl group or the like, in particular, by F, and the values ​​of m, p and n can be found in the invention summary. The terminal group in the above structure can be any group, and this application does not limit this.

[0316] The polymer material structure can be obtained by combining any one, two or more of the above-mentioned polymer units in a block, alternating or random arrangement, and these polymer material structures are also within the protection scope of the present application.

[0317] The raw materials for which the preparation methods are not described in the examples are all existing raw materials and can be purchased. The raw materials and preparation processes for which the preparation methods are described are all prior art, and the raw material preparation methods are not within the scope of protection of this application, and therefore are not described in detail in the specification.

[0318] It should also be noted that the applicant has conducted a large number of tests on this series of structures. Sometimes, in order to better compare with the existing system, the same structure and system have been tested more than once. Therefore, there may be certain errors in different tests.

[0319] Finally, it should be noted that the above-described embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

[0320] It should be noted that the compounds without preparation methods in the examples can be purchased on the market or synthesized according to existing synthesis routes, so they are not described in detail here.

[0321] The preferred specific implementation modes and embodiments of the present application are described in detail above in conjunction with the accompanying drawings, but the present application is not limited to the above implementation modes and embodiments, and various changes can be made within the knowledge scope of those skilled in the art without departing from the concept of the present application.

Claims

1. A polymer material, characterized in that The structure of the polymer material is: or ; Wherein, M1 is selected from C, M2 is selected from C; M3 is selected from C, and M4 is selected from C; R1-R4 are independently selected from any one of a chain or a ring with no, with or without a substituent; R5-R6 are independently selected from any one of a chain or a ring having no, a substituent or a substituent; represents a ring structure with any two adjacent positions being P and O, The P atom in is directly connected to the C atom; A1 indicates that any position of the ring structure can be substituted by a substituent; The cyclic structure represented by is selected from a single ring, or any one of a linked ring and a combined ring formed based on the single ring; The monocyclic ring is selected from saturated or unsaturated five- to six-membered rings, and the linked rings and fused rings are independently composed of two or more saturated or unsaturated five- to six-membered rings; the atoms on the rings are selected from C, P, S, N or O; m is selected from 1, indicating that there is one in every 1 / m -[M1-M2]-polymer units. Connected to M1 or M2; p is selected from an integer between 10 and 10000, representing the degree of polymerization of -[M1-M2]-polymerization unit; R3 is ; Among them, R 31 Selected from C; R 32 , R 33 are independently selected from none, or a chain consisting of 1-3 atoms, R 32 Connected to R1, R 33 Connected to P; R 34 is selected from H or a substituent; R7-R 11 Independently selected from any one of a chain or a ring with no, a substituent or a substituent; wherein R9 is selected from: , , , , , , , where A1 and A2 represent that the atoms in the ring / chain can be replaced by substituents; n is an integer selected from 5 to 1000, representing the degree of polymerization of the -[M3-M4]- polymerized unit; And p>n; The chain described by R1-R6 is selected from chains of 1 to 15 atoms, including saturated carbon chains, unsaturated carbon chains, saturated hetero chains, and unsaturated hetero chains; the atoms located on the chain are selected from C, S, N, O, and P.

2. The polymer material according to claim 1, characterized in that R 34 Selected from Li or BF3Li.

3. The polymer material according to claim 1, characterized in that The ring structure is selected from: 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 ; Here, A1, A2, and A3 represent that any position on the ring can be substituted with a substituent.

4. The polymer material according to claim 3, characterized in that The ring structure is selected from a fused ring formed by 2 or 3 of the single rings.

5. The polymer material according to claim 4, characterized in that The adjacent ring to which P and O are located contains at least one heteroatom or is substituted by at least one substituent containing a heteroatom, wherein the heteroatom is selected from N, O, P, S, Si, and F.

6. The polymer material according to any one of claims 1 to 5, characterized in that H1 represents a single -[M1-M2]-polymer unit , with H2 representing a single -[M3-M4]-polymer unit , in the polymer material, the arrangement of H1 and H2 is selected from any one or a combination of the following: Arranged in blocks: H1-H1- H1-H1-H1-H2-H2-H2- -H2-H2; Arranged in an alternating manner: one or more H1s and one or more H2s are arranged alternately in sequence; Arrange in a periodic manner: multiple periods are formed by one or more H1 and one or more H2, and the multiple periods are arranged in sequence; Arranged in a gradient manner: the composition of H1 and H2 changes gradually along the chain; Irregular arrangement: one or more H1s and one or more H2s are randomly arranged in an alternating manner.

7. The polymer material according to any one of claims 1 to 5, characterized in that In the structure of the polymer material, p is selected from an integer between 30 and 8000, and n is selected from an integer between 10 and 800.

8. The polymer material according to any one of claims 1 to 5, characterized in that The polymer material is formed by copolymerization of at least raw material A and raw material B; The structure of raw material A is , the structure of raw material B is .

9. An electrolyte, characterized in that The electrolyte comprises the polymer material according to any one of claims 1 to 8, or comprises the raw material for preparing the polymer material according to claim 8.

10. A battery, characterized in that: The battery comprises any one or more of the following: the polymer material according to any one of claims 1 to 8, the raw material for preparing the polymer material according to claim 8, and the electrolyte according to claim 9.

11. The battery according to claim 10, characterized in that The battery is a hybrid solid-liquid battery or an all-solid-state battery.

12. Use of the polymer material according to any one of claims 1 to 8 in a battery, characterized in that: Placing the polymer material in a battery component or a battery cell of the battery, and preparing the battery by an ex-situ curing process; Or the raw materials for preparing the polymer material are placed in the battery assembly or battery core of the battery, and the battery is prepared by an in-situ curing process; wherein the battery assembly includes electrodes, a separator and an electrolyte membrane.

13. The use according to claim 12, characterized in that The non-in-situ curing method of placing the polymer material in the battery includes: (1) placing the polymer material in the battery cell; specifically comprising: first adding the polymer material into an electrolyte to dissolve it, and then injecting it into the prepared battery cell; (2) Placing the polymer material in a battery component of the battery; specifically comprising: The polymer material is dissolved in a solvent and then coated on an electrode sheet, a diaphragm or formed into a separate film to form an electrode sheet, a diaphragm or an electrolyte membrane with a polymer material coating; or the polymer material is mixed in positive and negative electrode slurries to form a pole sheet containing the polymer material.

14. The use according to claim 12, characterized in that The in-situ curing method of placing the raw material in the battery includes: (1) placing the raw materials in the battery cell of the battery; specifically, the raw materials and the initiator are added to the electrolyte, and the solidification is performed in situ to form a solid-state battery with an integrated battery cell; or at least one of the raw materials is pre-placed in a battery assembly, the initiator and the remaining raw materials are added to the electrolyte, and then injected into the prepared battery cell, and the solidification is performed in situ to form a solid-state battery with an integrated battery cell; (2) Placing the raw material in a battery assembly of the battery; specifically comprising: The raw materials are prepared into a precursor solution and coated on an electrode sheet, a diaphragm or a separate film, and in-situ cured to form an electrode sheet, a diaphragm or an electrolyte membrane with a polymer material coating; or the raw materials are mixed into positive and negative electrode slurries and in-situ cured to form a pole sheet containing a polymer material.

15. The use according to claim 13, characterized in that The solvent includes one or more of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, butylene carbonate, methyl propyl carbonate, methyl formate, ethyl formate, propyl formate, butyl formate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, 8-valerolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 4-methyl-1,3-dioxolane, 2-methyl-1,3-dioxolane, ethylene glycol dimethyl ether and 1,3 dioxolane, cyclopentane, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, petroleum ether, acetone, ethanol, and acetonitrile; In the process of dissolving the polymer material in the solvent, an auxiliary agent is also added, and the auxiliary agent includes any one or more of the following: lithium salt, inorganic oxide particles, and fast ion conductor.

16. The use according to claim 15, characterized in that When the raw materials include raw material A and raw material B, the molar ratio of raw material B to raw material A is 0.01-1, and the total mass of raw material A and raw material B accounts for 1%-80% of the total mass of the precursor solution.

Citation Information

Patent Citations

  • Lithium battery polymer gel electrolyte

    CN108682863A

  • Flame retardant, preparation method and application thereof

    CN109734746A

  • Electrolyte and battery

    JP2007250191A

  • Reactive phosphorus compound and method for producing the same

    JP2009167114A